UJI DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL VARIETAS SORGUM: Sorgum verietas Numbu, sorgum varietas kawali, pupuk NPK - ANNISA INTAN AYU TRISNALIVIA; Santosa, Sartono Joko; Siswadi, Siswadi (innofarm, 2023)
This research aims to test the best NPK fertilizer dose on sorghum varieties' growth and yield (Sorghum bicolor L.). The research design used is a Complete Randomized Group Design (RAKL) arranged in a split plot consisting of 2 factors, two factors as follows: Factor Type of Sorghum Plant Variety as the main plot, which consists of 2 varieties as follows: V1 = sorghum variety Numbu and V2 = sorghum variety Kawali. The second factor is the Dosage of NPK Fertilizer as a subplot, which consists of 5 levels as follows: N0 = 0 g NPK Fertilizer Dose (Control), N1 = 1.5 g NPK Fertilizer Dose, N2 = 3.0 g NPK Fertilizer Dose, N3 = 4.5 g NPK Fertilizer Dose, N4 = 6.0 g NPK Fertilizer Dose. The parameters observed were height of plant, number of leaves, fresh weight of stalks, dry weight of stalks, number of panicles per plant, weight of panicles per plant, number of seeds per panicle, and weight of grains per panicle. The results showed that the application of Pak Tani NPK fertilizer with a dose of 250 kg/ha (3.0 gr/plant) gave the best results in sorghum variety Numbu (V1) can be seen in the observation of plant height eight weeks after planting with an average of 188.22 cm, fresh weight of stalks with an average of 949.92 gr and dry weight of stalks with an average of 224.36 gr. The best results in the Kawali variety (V2) can be seen in the observation of the importance of panicles per plant, with an average of 104.84, the number of seeds per plant, with an average of 1961.22 and the weight of seeds per plant with an average of 93.73.